A theoretical investigation of photoacoustic contrast agents. - Firouzi, K; Stride, E; Saffari, N (2013)
Photoacoustic imaging offers significant potential as a biomedical imaging modality. For some applications, however, there is a need for contrast enhancement. In this paper, a theoretical comparison is presented of the efficacy of three different designs for photoacoustic contrast agents (PACAs), specifically, a droplet of dye, a bubble filled with gas coated by a dye loaded shell, and a droplet of volatile dye. For each case, the governing equations describing the dynamics of a single PACA in a homogenous incompressible fluid are derived. The coupled sets of equations describing the bubble oscillation and resulting radiated pressure, the photo-acoustic energy equation, and the equation of state are then solved numerically. The numerical results predict a stronger radiated acoustic signal for the same optical source energy density in the case of the volatile dye droplet by a factor of up to two orders of magnitude compared with the other two types of agent.